(untitled) (Revista Interdisciplinar Pensamento Científico, 2022)
Sea turtles are one of the many marine species in constant threat by the human population. To help the species conservation, studies based on stranded turtles found in coastal areas are crucial, since they can provide important data about the cause of death. Therefore, we evaluated the stranding patterns that occur in a South American region, on the southeast coast of Brazil, from 2011 to 2016. Our findings show that dead or alive stranded turtles exhibit different stranding patterns, which might be explained by oceanographic processes (like coastal/oceanic currents and upwelling), nutrient enrichment in coastal areas, and biological factors (like parasitosis and plastic debris ingestion). We expect the results presented here, shall shed light on this issue and contribute to the development of intervention plans to diminish life-threatening problems to sea turtles.